Exploring EFL Students Learning Motivation and Activeness in the Extensive Reading Classroom through Task-Based Learning - Terasne*, Terasne; Permana, Dira; Hanan, Ahmad (Riwayat: Educational Journal of History and Humanities, 2023)
This research is motivated by the assumption that Task Based Learning (TBL) is an old method that is no longer relevant in the world of education. The purpose of study was to determine to what extent TBL contributed to the students motivation and students activeness in extensive reading classroom through TBL at fifth semester students of Faculty, Culture, Management and Business, Mandalika University of Education. The technique of data collection used was: (1) the questionnaire consisted of twelve statements based on steps of TBL namely; pre-task, during-task and post-task. Technique of data analysis use was data reduction, data display and data conclusion. To determine frequency of the students motivation and activates trough TBL using the formula. The results of questionnaire shows that from 30 students, there were thirteen students or 43% who were included in the motivated category. It can be concluded that the fifth semester students of the Faculty of Culture, Management and Business are motivated in extensive reading classroom through TBL. (2) Observation, to find out how active students are in extensive reading classroom through TBL. Observation data was analyzed qualitatively in the form of statements that describe students activates. From the result of observation shows a total percentage of 91.37. It can be concluded that the fifth semester students of the Faculty of Cultural, Management and Business are active enough in extensive reading classroom through TBL.